Growth and carcass traits of two rabbit genotypes: comparison of Slovene SIKA male line with commercial hybrids - Kermauner, Ajda; Žgur, Silvester (Acta Agraria Kaposváriensis, 2002)
Growth rate and carcass traits of two rabbit genotypes (SIKA male line - Slovenian male line for meat production and commercial hybrid imported from Italy, 50 rabbits per genotype and 50 rabbits of each sex) were as recorded from weaning (41 ± 1 day) to slaughter. Rabbits were fed standard feed mixture Kun/stand ad libitum. Thirty-six rabbits were slaughtered at 77th day and 40 rabbits at 90th day. For carcass evaluation 16 animals per genotype, age and sex were selected. SIKA rabbits reached significantly higher weight at 90 days (2933 vs. 2711 g) and significantly better feed conversion ratio than Italian hybrids (4.085 vs. 4.711 g). SIKA rabbits exhibited significantly lower kidney fat percentage (2.24%) than Italian hybrids (2.90%). There were no differences in percentage of different carcass cuts, pH 24 and meat colour between two genotypes. Increased animal age at slaughter from 77 to 90 day’s did not change kidney fat percentage.